Effect of Work Environment Ethics and Organizational Justice on Employment Engagement through Organizational Trust in Inspired Health Centers, Magelang Regency - Indoyo, Bayu Adjie; Ranihusna, Desti (Universitas Negeri Semarang, 2022)
This study aims to examine the effect of work environment ethics, organizational justice, and organizational trust on work engagement as well as examine the mediating effect of organizational trust on the relationship between work environment ethics and organizational justice on work engagement. The object of this research is a health center in Magelang Regency. The sample used in this study was 119 respondents with a total sampling technique. The analysis used is descriptive and statistical analysis using SmartPLS 3.0 software. The results of the study show that work environment ethics has a significant effect on work engagement, organizational justice and organizational trust have no significant effect on work engagement. In addition, organizational trust did not succeed in mediating the relationship between work environment ethics and organizational justice on work engagement. Suggestions for health centers to maintain and continue to improve work engagement with health workers by conducting routine behavioral audits of health workers, improving work environment facilities, and building supportive working conditions, especially health workers who work on night shifts.